Methodological features of the use of hand motor actions in the correction of preschool children’s hand disorders ("Ant" stand) - Kantarzhi Vitaliy (State institution “South Ukrainian National Pedagogical University named after K D. Ushynsky”, 2020)
Craft therapy (or ergotherapy) in a physical rehabilitation of children with musculoskeletal system disorders has a great importance both as a method of overcoming existing motor disorders and as the basis for the future successful socialization of these children. In the available literature, the issues of craft therapy use in combination with physical education of pre-schoolers in various institutions of preschool education are insufficiently and non-systematically covered. This makes this article relevant. The article discusses the methodological possibilities of using the author's work simulator the "Ant" for the correction of hand dysfunctions of pre-schoolers by means of physical education and craft therapy. The main technical characteristics of the simulator and the features of its manufacture are presented. The characteristics of the "Ant" versatility and its multifunctionality are given, which ensures the success of its use in a kindergarten of any kind. The properties of the "Ant" stand for improving the psychophysical development of pre-schoolers are listed. The formulated methods of using the “Ant” simulator and the methodological techniques for correcting the main hand functions of the pre-schoolers (tested in the process of the ascertaining experiment) have a particular value. The main methods included the ones as follows: game stimulation, objectivity (subject-manipulative activity), instrumental logic, hand-eye coordination, an individually differentiated approach to the correction of hand disorders of children by means of physical education and craft therapy. Each of the listed methods includes a number of methodological techniques that increase the effectiveness of corrective instrumental-subject manipulations. The prospects of further research in this area are seen in the elaboration of new work simulators for preschool children suffering from disorders of the musculoskeletal system alongside the creation of the necessary methodological support for their effective use.